The Influence Of Product Quality, Price And Service Quality On Consumer Satisfaction (Coffeetree Case Study In Medan) - M. Fiqih Syahputra G.; Husni Muharram Ritonga; Hernawati Lubis (CERED Indonesia Institute, 2022)
This study aims to determine whether product quality, price and service quality simultaneously have a positive and significant effect on consumer satisfaction at Kopitree in Medan. The data analysis technique used is the associative quantitative method with the help of the SPSS program. This study uses multiple linear regression. The research sample was 68 respondents. Primary data collection using a questionnaire. The results showed that product quality partially had a positive and significant effect on consumer satisfaction at Kopitree in Medan. Price partially has a positive and significant effect on consumer satisfaction at Kopitree in Medan. Service quality partially has a positive and significant effect on customer satisfaction at Kopitree in Medan. Product quality, price and service quality simultaneously have a positive and significant effect on consumer satisfaction at Kopitree in Medan.